Cardinal Contarlni at Regensburg: a study in ecumenism, Catholicism and curialism - Matheson, Peter Clarkson (The University of Edinburgh, 1968)
Since the end of the twenties, since the initiation of Visitations in Electoral Saxony, since the Diet of Speyer,the Reformation had been clothing itself in quite definitely confessional garb. Emergent Protestantism witnesses to the disruptive and creative influence of the Reformation on the totality of political, social, and cultural life. If, however, Protestantism was a political and cultural phenomenon as well as an ecclesiastical one, the same is true of Catholicism. What confronted one another at the Diet of Regensburg in 1541 were not only two theological alternatives but also two cultural and political alternatives. Of these two alternatives it is the Protestant one which, understandably, has received the more generous attention. Yet pre-tridentine Catholicism is not without its own peculiar interest, is by no means all disintegration and confusion. The Machiavellianism of Curial diplomacy is as much in line with the trend of things to come as the Erasaianism of the Imperial Court. Even the traditionalist component to pre-tridentine Catholicism is by no means an undifferentiated quantity. Contarini's activity at Regensburg mirrors the richness and elusiveness of this Catholicism. The very fact of his presence at the Diet cannot be wondered at enough. It is at least as significant as the eventual failure of his mission. For if it was the inner contradictions of pre-tridentine Catholicism, as exemplified in Contarini, which were to be so cruelly exposed by the Diet, it was these same contradictions which had enabled an exercise in reconciliation to take place at all. Contarini may have understood something of Lutheran theology. Of Protestantism he had not the slightest comprehension. His ecumenical concern and his understanding of Justification prepared him only to deal with the former. Hence his retreat when faced by the full implications of a Protestant Church and a Protestant culture, first to a confessional Catholicism, and then to an intolerant Curialism. The dialogue between Protestantism and Catholicism at the Diet of Regensburg in 1541 did not fail. It never took place.
Keywords: Catholic; curia; Protestant; Diet of Regensburg